Arctic amplification has already peaked - Richard Davy; Philipp Griewank (Environmental Research Letters, 2023)
It has been demonstrated that the Arctic has warmed at almost four times the global average rate since 1979, a phenomenon known as Arctic amplification. However, this rapid Arctic warming is tightly linked to the retreat and thinning of summer sea ice, and so may be expected to weaken as the Arctic transitions to seasonal ice cover. Here we show evidence from gridded observations and climate reanalysis that Arctic amplification peaked sometime in the early 2000s. This occurred concurrently with a maximum in the rate of loss of sea ice area, thickness, and volume. From CMIP6 projections and the CESM2 large ensemble we see that Arctic amplification is unlikely to be so high again at any future point in the 21st century except in the lowest emissions scenarios in which global temperatures stabilize while the Arctic continues to warm.